1990
DOI: 10.1007/bf02365471
|View full text |Cite
|
Sign up to set email alerts
|

Mussel beds — amensalism or amelioration for intertidal fauna?

Abstract: The faunal assemblages of a mussel bed (Mytilus edufis L.) and ambient sand_flat were compared to study how a bioherm of suspension feeding organisms affects benthic communities in a tidal flat. During a survey of mussel beds in the Wadden Sea at the island of Sylt {North Sea}, a total of 52 macrofaunal species and 44 meiobenthic plathelminth species were detected. They occupied different microhabitats in the mussel bed. 56 % of the macrofauna species were dwelling in the sediment beneath the mussels and 42 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
5
10

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 31 publications
12
60
5
10
Order By: Relevance
“…Historically, however, these regions would have supported widespread populations of O. edulis (Reise et al, 1989;Riesen and Reise, 1982 edulis may have formed massive reefs in historic periods (Todorova et al, 2009) there are no contemporary records of it forming reefs. Species diversity is related to habitat heterogeneity, generally following a unimodal curve, with greatest diversity usually in habitats with intermediate levels of heterogeneity (Allouche et al, 2012;Dittmann, 1990;Snover and Commito, 1998). Although no decrease of diversity was associated with increasing oyster cover in the present study, previous studies have shown lower species richness in experimental plots with high oyster cover compared to those with low oyster abundance (Green and Crowe, 2013).…”
Section: Discussioncontrasting
confidence: 64%
“…Historically, however, these regions would have supported widespread populations of O. edulis (Reise et al, 1989;Riesen and Reise, 1982 edulis may have formed massive reefs in historic periods (Todorova et al, 2009) there are no contemporary records of it forming reefs. Species diversity is related to habitat heterogeneity, generally following a unimodal curve, with greatest diversity usually in habitats with intermediate levels of heterogeneity (Allouche et al, 2012;Dittmann, 1990;Snover and Commito, 1998). Although no decrease of diversity was associated with increasing oyster cover in the present study, previous studies have shown lower species richness in experimental plots with high oyster cover compared to those with low oyster abundance (Green and Crowe, 2013).…”
Section: Discussioncontrasting
confidence: 64%
“…Dittmann 1990;Obert and Michaelis 1991;Albrecht and Reise 1994;Günther 1996;Albrecht 1998) or subtidal mussel beds (e.g. Dekker 1989;Dankers and Zuidema 1995).…”
Section: Effect Of Tidal Levelmentioning
confidence: 99%
“…These mussel beds are abundant in the lower tidal zone and subtidally (Verwey, 1954;Riesen & Reise, 1982;Dankers & Koelemaij, 1989;Obert & Michaelis, 1991), constituting ecological elite structures in terms of the high number of associated species (Dittmann, 1990), biomass and secondary production (Asmus, 1987), foraging site for birds (Swennen et al, 1989;Zwarts, 1983), remineralization, and oxygen consumption (Dame & Dankers, 1988;Asmus et al, 1990).…”
Section: Introductionmentioning
confidence: 99%